Vibration response of cable for submerged floating tunnel under simultaneous hydrodynamic force and earthquake excitations. Issue 11 (August 2018) - Wu, Zhiwen; Ni, Pengpeng; Mei, Guoxiong
A simplified analysis model of cable for submerged floating tunnel subjected to simultaneous hydrodynamic force and earthquake-excited vibrations in an ocean environment is proposed in this study. The equation of motion of the cable is obtained by a mathematical method utilizing the Euler beam theory and the Galerkin method. The hydrodynamic force induced by earthquake excitations is formulated to simulate real seaquake conditions. Random earthquake records are generated in the time domain by the stochastic-phase spectrum method. The cable for submerged floating tunnel is then subjected to combined hydrodynamic force and earthquake excitations. A sensitivity study is performed to assess the influence of key parameters, including hydrodynamic, earthquake, and structural parameters, on the dynamic response of the cable. It has been observed that the ratio of parametric frequency to natural frequency, the direction and magnitude of earthquake excitation, the initial tension in the cable, and the damping ratio all have significant influences on the hydrodynamic and seismic response of the cable. Therefore, these effects must be considered rigorously during the design of anchor systems for submerged floating tunnel.